2016
DOI: 10.4103/2211-4122.178467
|View full text |Cite
|
Sign up to set email alerts
|

Isolated congenital left ventricular diverticulum: A case report and differential diagnosis

Abstract: We describe a case of an incidental finding of diverticulum in a patient presented to the Emergency Department for atypical chest pain, and we analyze the challenging differential diagnosis with aneurysm, pseudoaneurysm, and ventricular cleft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The cleft is localized in the compacted myocardial layer and with contractions usually gets obliterated during systole. These characteristics also make clefts difficult to visualize using echocardiograms [ 5 ]. A ventricular septal defect can also be mistaken with LVD (yet it is the most commonly associated defect) because of the difficult visualization of the apex and surrounding structures using an apical four-chamber view.…”
Section: Discussionmentioning
confidence: 99%
“…The cleft is localized in the compacted myocardial layer and with contractions usually gets obliterated during systole. These characteristics also make clefts difficult to visualize using echocardiograms [ 5 ]. A ventricular septal defect can also be mistaken with LVD (yet it is the most commonly associated defect) because of the difficult visualization of the apex and surrounding structures using an apical four-chamber view.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and surgical intervention for this pathology might be lifesaving. 9 Vazquez-Jimenez et al published a literature review of 153 Cantrell's Pentalogy cases in 1998. According to the analysis, a ventricular septal defect was the most common cardiac malformation (72%).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported closure of the diverticulum neck with a patch, with surgical glue closure and plication with aneurysmorrhaphy. 8 Other authors have described their technique as suture reapproximation in a double-layered fashion with the use of felt, 9 while some describe removal of the outpouching cavity and closure with an in-situ patch. 10 Due to the catastrophic events associated with CLVD, our institution prefers surgical management for patients with symptomatic CLVD.…”
Section: Commentmentioning
confidence: 99%